1999
DOI: 10.1046/j.1365-2125.1999.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid development of tolerance to dipyridamole‐associated headaches

Abstract: The rapid decrease in the incidence of headaches over time implies that most patients quickly develop tolerance to dipyridamole-associated headaches. Appropriate information given to the patient when prescribing and dispensing dipyridamole/ASA may reduce early withdrawals from treatment and increase compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 12 publications
0
27
1
Order By: Relevance
“…In these studies, headache was also the main reason for discontinuation of the dual therapy. Yet another study with DP found 2 out of 3 patients with headache on the first day of treatment but only 3% on the fifth day of treatment [13]. The headache peaked 2–3 h after the administration coinciding with the peak of the plasma concentrations of DP with no relation to interindividual differences due to pharmacokinetic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, headache was also the main reason for discontinuation of the dual therapy. Yet another study with DP found 2 out of 3 patients with headache on the first day of treatment but only 3% on the fifth day of treatment [13]. The headache peaked 2–3 h after the administration coinciding with the peak of the plasma concentrations of DP with no relation to interindividual differences due to pharmacokinetic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly tolerance for this side effect builds up, but the exact mechanism is unknown [3]. The duration of headache varies from 2 to 10 days [3,4,5,9].…”
Section: Introductionmentioning
confidence: 99%
“…The duration of headache varies from 2 to 10 days [3,4,5,9]. Although the appearance of headache is not linked to the pharmacokinetic profile of the drug, it may possibly be associated with plasma peak concentrations [3]. …”
Section: Introductionmentioning
confidence: 99%
“…However, a substantial number of patients complain of headache shortly after starting treatment. The nature, frequency and severity of dipyridamole-induced headache have been characterized [2]. The headache occurs shortly after the first dose, tends to occur more frequently in healthy subjects, and wanes in frequency and severity over 3–5 days in the majority of subjects.…”
Section: Introductionmentioning
confidence: 99%